Untangling inconsistent magnetic polarity records through an integrated rock magnetic analysis: A case study on Neogene sections in East Timor - F. M. Aben; M. J. Dekkers; R. R. Bakker; D. J. J. van Hinsbergen; W. J. Zachariasse; G. W. Tate; N. McQuarrie; R. Harris; B. Duffy (Geochemistry, Geophysics, Geosystems, 2014)
Abstract Inconsistent polarity patterns in sediments are a common problem in magnetostratigraphic and paleomagnetic research. Multiple magnetic mineral generations result in such remanence “haystacks.” Here we test whether end‐member modeling of isothermal remanent magnetization acquisition curves as a basis for an integrated rock magnetic and microscopic analysis is capable of isolating original magnetic polarity patterns. Uppermost Miocene‐Pliocene deep‐marine siliciclastics and limestones in East Timor, originally sampled to constrain the uplift history of the young Timor orogeny, serve as case study. An apparently straightforward polarity record was obtained that, however, proved impossible to reconcile with the associated biostratigraphy. Our analysis distinguished two magnetic end‐members for each section, which result from various greigite suites and a detrital magnetite suite. The latter yields largely viscous remanence signals and is deemed unsuited. The greigite suites are late diagenetic in the Cailaco River section and early diagenetic, thus reliable, in the Viqueque Type section. By selecting reliable sample levels based on a quality index, a revised polarity pattern of the latter section is obtained: consistent with the biostratigraphy and unequivocally correlatable to the Geomagnetic Polarity Time Scale. Although the Cailaco River section lacks a reliable magnetostratigraphy, it does record a significant postremagnetization tectonic rotation. Our results shows that the application of well‐designed rock magnetic research, based on the end‐member model and integrated with microscopy and paleomagnetic data, can unravel complex and seemingly inconsistent polarity patterns. We recommend this approach to assess the veracity of the polarity of strata with complex magnetic mineralogy.